Proceedings of the 2nd International Conference on Tourism, Gastronomy, and Tourist Destination (ICTGTD 2018) 2018
DOI: 10.2991/ictgtd-18.2018.28
|View full text |Cite
|
Sign up to set email alerts
|

Modeling The Demand for inbound Tourism to Thailand: Panel Data Approach

Abstract: This paper models the inbound tourism demand of Thailand by focusing on six major tourism markets, including China, Malaysia, South Korea, Japan, Russia, and India. Several economics variables widely used in the demand modeling literature were adopted. Besides, additional variables pertaining to environmental and security aspect were considered and incorporated into our investigated model. The panel data of six countries during 2003 and 2015 were collected from various sources. In our analysis, the random effe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 26 publications
0
2
0
Order By: Relevance
“…This indicator referred to the rate of international openness, which was a direct effect on the types of meeting tourism, conference tourism, even exhibition tourism. Additionally, stated by Preedatham et al (2018) , domestic prices in markets and safety travels are concluded to be factors improving tourism demands in Thailand’s tourism sectors. Tran et al (2020) also concluded the best solution for stimulating tourism sectors is safety, prevention, and control.…”
Section: Literature Reviewmentioning
confidence: 99%
“…This indicator referred to the rate of international openness, which was a direct effect on the types of meeting tourism, conference tourism, even exhibition tourism. Additionally, stated by Preedatham et al (2018) , domestic prices in markets and safety travels are concluded to be factors improving tourism demands in Thailand’s tourism sectors. Tran et al (2020) also concluded the best solution for stimulating tourism sectors is safety, prevention, and control.…”
Section: Literature Reviewmentioning
confidence: 99%
“…According to Preedatham, Vivatvanit, and Suksonghong (2018), the 2003-2015 panel data of six countries were obtained from various sources, with the random effects model appropriately implemented with the dataset. The coefficient estimates were then computed using the panel least square method.…”
Section: Literature Reviewmentioning
confidence: 99%